2019
DOI: 10.1177/0165551519861605
|View full text |Cite
|
Sign up to set email alerts
|

Music-search behaviour on a social Q&A site: A cross-gender comparison

Abstract: While there have been numerous studies of music-search behaviour, little is known about gendered aspects of how it is carried out on social question and answer sites. The article examines gender differences manifested on one such site with regard to (a) the motivations of the person posing the question, (b) intervening variables that influence music-search behaviour and (c) the formulation of the questions. Results from manual categorisation and other analysis of 17,380 music-relevant questions collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The similar situation also exists in the context of social Q&A sites. When asking questions in such sites, Deng et al (2019) found that males tended to conduct task-oriented behaviors, such as including context information in questions asking for ready reference, whereas females exhibited in a socially oriented manner. Female users usually ask questions in a second-person pronoun aiming for promoting discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The similar situation also exists in the context of social Q&A sites. When asking questions in such sites, Deng et al (2019) found that males tended to conduct task-oriented behaviors, such as including context information in questions asking for ready reference, whereas females exhibited in a socially oriented manner. Female users usually ask questions in a second-person pronoun aiming for promoting discussion.…”
Section: Introductionmentioning
confidence: 99%